Impact of Indian mustard growth and incorporation on annual weed population dynamics and communities. (7th May 2019) - Lefebvre, M; Leblanc, M L; Watson, A K
Summary: Biofumigation from Brassica cover crops may be used to control soilborne pests and weeds. A study was conducted to understand the influence of biofumigation on key processes of annual weed population dynamics. Five combinations of Indian mustard (M) and oat (O) cover crop treatments were assessed in a 3 year field study at two locations in Québec, Canada. Treatments included four spring/fall cover crop combinations (M/M, M/O, O/M, O/O) and a weedy check control with no cover crop. Prior to mowing and incorporation of cover crops, weed identification, count and biomass measurements were recorded to evaluate the total weed density, to calculate the relative neighbour effect (RNE) and weed diversity metrics and to perform principal co‐ordinates analyses. Indian mustard cover crops had no impact on weed establishment in 2014 due to low biofumigant potential compared to the oat cover crop. In 2015 and 2016, Indian mustard isothiocyanate (ITC) production increased and weed establishment within the Indian mustard cover crop decreased. Moreover, post‐cover crop incorporation decreased the next year spring weed emergence. Allelopathic interference of Indian mustard was significant when plant tissues produced more than 600 μg of allyl‐ITC g −1 . It is now possible to rationalise the use of Brassica cover crops and biofumigation for weed control with an enhanced understanding of the impact of biofumigation on key processes of weed population dynamics.